اللاجئون بين الحل القانوني والواقع السياسي في بلد الإقامة - حسن, محمد جلال; زوراب, سيفان صالح (Sulaimani Journal for Humanities, 2022)
In todays' world we are witnessing an unprecedented level of human mobility. The number of people who live today in countries other than the ones in which they were born is greater than ever before, and there are refugees and migrants in all countries of the world, where the suffering of refugees is almost similar, with its human dimensions that become crueler when prolonged. With the extending the crisis, the human are become weak, and that when it pushes with collective human mobility, the United Nations High Commissioner for Refugees (UNHCR) classifies them (refugees) as groups of people in a vulnerable situation, forcibly fleeing from the crisis, reaching the cross-border areas of the diaspora in order to save their lives. Flow of the Iraqi and Syrian immigrants into Turkish territory is not something new or surprising, as Turkish immigration policies began to change gradually since the mid-2000 to be representative of European Union policies. In view of the exacerbation of the refugees' problem in todays' world, it is necessary to shed light on the rights of those refugees and their legal protection provided by international law within the national legislation framework. In order to compel the parties related to respecting human rights and reducing the effects of these conflicts, the availability of a legal solution in the face of the political reality in the country of asylum, and the extent to which the asylum-seeker has the legal status of a refugee until their application is decided by those countries they will remain in. Working to promote the rights of refugees and the protection system guaranteed in the international laws, remains dependent on the ability of the international community to address the real causes, which lead to the birth and exacerbation of the phenomenon of asylum. As a result, this research comes in the same context, which is the definition of the efforts of the international human rights inheritance of what is asylum and the right of asylum and its similar designations, texts and legal provisions that relate to their rights, as mentioned in the Iraqi refugee law, the human rights law, and international humanitarian law, as it cares In classifying the target groups and beneficiaries of refugee laws, and exploring the scope of expansion in refugee situations, and necessarily looking at the content of the relationship between refugees and the receiving countries, and the extent of the host country’s structure in terms of mutual obligations, as the state’s has right to be concern about its-own national sovereignty, national security, and securing its national economy, as well as understanding that interconnected relationship between those sectors on the refugee situations, and finally dealing with the implications of politicizing refugee problems and its effects on the future of international